2018
DOI: 10.1097/bsd.0000000000000659
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Decompression, Decompression Plus Fusion, and Decompression Plus Stabilization for Degenerative Spondylolisthesis

Abstract: Study Design:This is a prospective, randomized controlled trial.Objective:To prospectively assess the long-term clinical results of decompression alone, decompression plus fusion, and decompression plus stabilization for degenerative spondylolisthesis.Summary of Background Data:Symptoms of lumbar spinal stenosis due to degenerative spondylolisthesis originate from compression of the dural sac or nerve root. Essentially, this condition is treated by performing a decompression of neural structures. Posterolatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 27 publications
1
79
0
3
Order By: Relevance
“…38 Similarly, in randomized controlled trials of patients with lumbar spinal canal stenosis, with or without degenerative spondylolisthesis, decompressive surgery followed by the placement of posterior instrumentation did not result in better clinical outcomes after 2 and 5 years of follow-up than decompressive surgery alone. 23,36,39 Notably, Daubs et al compared the duration of the symptom-free results after decompression alone with decompression and fusion surgery in patients with mild degenerative lumbar scoliosis (< 30°) and stenosis after long periods of time. At 5 years postoperatively, 12 (75%) of the 16 patients in the decompression-alone group developed recurrent stenosis versus only 14 (36%) of 39 patients in the decompression and fusion group (p = 0.016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Similarly, in randomized controlled trials of patients with lumbar spinal canal stenosis, with or without degenerative spondylolisthesis, decompressive surgery followed by the placement of posterior instrumentation did not result in better clinical outcomes after 2 and 5 years of follow-up than decompressive surgery alone. 23,36,39 Notably, Daubs et al compared the duration of the symptom-free results after decompression alone with decompression and fusion surgery in patients with mild degenerative lumbar scoliosis (< 30°) and stenosis after long periods of time. At 5 years postoperatively, 12 (75%) of the 16 patients in the decompression-alone group developed recurrent stenosis versus only 14 (36%) of 39 patients in the decompression and fusion group (p = 0.016).…”
Section: Discussionmentioning
confidence: 99%
“…Since degeneration is a slowly occurring process, progressive instability might develop over time after decompression, and thus, long-term changes are clinically important as well, such as shown by the previously mentioned study by Daubs et al 19 However, several clinical studies with up to 5 years of follow-up show good clinical outcome, which suggests that the immediate effect of the surgical procedures by directly altering spinal biomechanics is greater than the slow effect of end-stage degeneration. 23,36,39 For posterior instrumentation, there were screws placed in L2 and L4, which were connected with bilateral rods. No screws were placed in L3, as this would increase the difficulty of placing the rods in the screws at this level due to the variety in Cobb angle of the lumbar spines.…”
Section: Discussionmentioning
confidence: 99%
“…The focus of controversy was whether the addition of fusion added benefit to decompression for patients with either grade I or II spondylolisthesis spondylolisthesis. Increasing evidence has demonstrated that in the management of DLS associated with spinal stenosis, additional fusion may not yield any clinical improvement over treatment with decompression alone (5)(6)(7).…”
Section: Efficacy Of Percutaneous Transforaminal Endoscopic Decompresmentioning
confidence: 99%
“…Any of the following complications: Dural tear, delusion, hematoma, meralgia, pulmonary embolism, misplacement of pedicle screw 11…”
Section: Type Of Outcomes Definition Examplesmentioning
confidence: 99%